Government Transformation in the 5.0 Era: Challenges and Adaptation Strategies - Hendri Wijaya, Junior; Sumarto, Rumsari Hadi (TheJournalish: Social and Government, 2024)
Government Transformation in the 5.0 Era brings significant challenges that require appropriate adaptation strategies to meet increasingly complex public expectations and evolving technology. In the face of these changes, the government needs to adopt a strategy that allows people to interact directly through social media, mobile applications, and other online platforms. The government needs to prioritize investment in reliable and secure digital infrastructure to support the efficiency of public services and improve service accessibility for all levels of society. Through literature studies, this article presents an in-depth analysis of the conceptual framework and relevant findings related to government transformation. By strengthening the understanding of adaptation challenges and strategies, this article is expected to contribute to guiding effective policy measures and practices to support government transformation in the 5.0 Era. By adopting strategies, the government can overcome the challenges faced in government transformation in the 5.0 Era and take advantage of the opportunities offered by technological advances to provide better and inclusive public services for the community.